Exploratory factor analysis of the Adapted Skillstreaming Checklist for children with autism spectrum disorder. (February 2020) - Lopata, Christopher; Donnelly, James P; Thomeer, Marcus L; Rodgers, Jonathan D; Volker, Martin A; Booth, Adam J
The Adapted Skillstreaming Checklist measures social/social-communication skills and behavioral flexibility/regulation of children with autism spectrum disorder without intellectual disability. Prior studies provided support for the reliability and criterion-related validity of the Adapted Skillstreaming Checklist total score for these children; however, no studies have examined the Adapted Skillstreaming Checklist factor structure. This exploratory factor analysis examined the factor structure and internal consistency of parent ratings on the Adapted Skillstreaming Checklist for a sample of 331 children, ages 6–12 years, with autism spectrum disorder without intellectual disability. Results yielded a correlated three-factor solution. The individual factors and total score demonstrated very good internal consistency reliability. Findings supported the presence and interpretability of three subscales, as well as derivation of a total composite reflecting overall prosocial and adaptive skills and behaviors. Implications for assessment and research are discussed.